Effect of Machine Parameters on Threshing Quality for Seed Crop of Chickpea - Sinha, J P; Dahliwal, I S; Sinha, S N (Journal of Agricultural Engineering, 2009)
Chickpea is an important pulse crop of Indian sub continent, but with low productivity. Non-availability of quality seeds is one of the major reasons for low productivitiy. Being dicotyledonous and the germ tip being located at the protruding structure, the seeds are prone to mechanical injuries during threshing. A study was conducted to investigate the effect of machine parameters on threshing quality for chickpea seed crop. The type of threshing element, cylinder speed and feed rate had significant effect on threshed seed quality as well as the performance of the thresher. Teflon coated iron beater threshing element at 8.94m/s cylinder speed at feed rate 200 kg/h was optimum for minimal visible and invisible injury of seeds. The threshing efficiency, thrower loss and cleaning efficiency was 98.96%, 0.95% and 91.93 %, respectively, and within acceptable limits. A radiographic index was developed to provide combined information of mechanical abused seed value.